Species Checklist and DNA Barcoding of Baung (Bagrid Catfish) Hemibagrus Hoevenii from Muar River, Johor - Bin Mohamad Rais, Haziq Ismat; Kamarudin, Kamarul Rahim; Mohd Zawawi, Mohamad Qamarul Abidin; Mohd Ghazali, Nurul Najihah; Lokman, Mohd Ilham Norhakim (Journal of Sustainable Natural Resources, 2023)
Of Asia, Africa, and the Middle East, there are 15 genera in the Bagridae family. The tropical freshwater catfish Hemibagrus hoevenii is found in Asian waters. Bagrids are also known as Old World pimelodids, while New World bagrids may be more accurate. In Muar, Johor, DNA barcoding has never been utilised to determine the species of bagrid catfish. Therefore, this study was done to update the species checklist of Baung (bagrid catfish) in Muar River, and DNA barcoding of protein-coding cytochrome c oxidase I (COI) mitochondrial gene was done for species identification and phylogenetic analyses. A number of two partial COI gene sequences ranging 674-687 nucleotide bases were successfully obtained for two specimens of Baung Lawi and the Nucleotide Basic Local Alignment Search Tool (BLAST) analysis suggested their species status as from the genus Hemibagrus. Furthermore, the results of the phylogenetic analyses showed that the neighbour joining tree, the maximum parsimony tree and the maximum likelihood tree grouped the COI mtDNA gene sequences of Baung Lawi from Muar River in one single cluster, thus confirming the species status and showed the presence of H. hoevenii in Muar River, Johor.